Study on the Feasibility of Oil Palm-Fronds for Biomass Gasification - Sulaiman, S. A. (2010)
As one of the world largest producer of palm oil, Malaysia has an abundant supply of oil-palm fronds due to the large plantation areas in the country. The fronds are pruned regularly but have little use and are mainly left on the ground in a huge quantity for natural decomposition which is a slow process. Considering their large and consistent supply, oil-palm fronds could be a promising source of biomass energy through gasification. There has been very scarce information on the characteristics of oil palm fronds, which is vital in deciding if such biomass is technically suitable for gasification. In the present work, the feasibility of oil-palm fronds for biomass gasification is studied. The study is conducted experimentally via standard tests to determine their thermo chemical characteristics. Ultimate analysis is conducted to determine the contents of carbon, nitrogen, hydrogen and sulphide in oil palm fronds. Proximate analysis is performed to identify the burn characteristics of the biomass. The energy content in the fronds is determined by using a bomb calorie meter. The ignitability of the fronds is also studied experimentally to assess the ease to start-up combustion of the fronds. The characteristics of the flame of the resulting syngas from gasification of oil palm fronds are qualitatively studied. The study is extended to computer simulation to predict composition of the syngas. Technically, it is found from this work that oil palm fronds are feasible for gasification and has a good potential as a renewable energy source.